2012
DOI: 10.5586/aa.2008.045
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cultivation conditions on growth, sporulation and formation of morphological structures of Topospora myrtilli (Feltg.) boerema

Abstract: The growth of Topospora myrtilli isolates, obtained in the years 2001-2003, was studied on PDA medium at -10, +2, +6, +12, +18, +22 and +28°C. The growth and sporulation of the isolates were observed at +22°C on the following culture media: PDA, maltose - MA and mineral - MSA, as well as on two versions of oat media, one containing 20 g of oat flakes per litre (OA-20), and the other containing 50 g of oat flakes per litre (OA-50). The observations of the linear growth of colonies of the studied strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…In classical phytopathological studies of various pathogens, research begins with the observation of the development of the disease (symptoms and etiological signs). The observations made during the presented studies fully confirmed the earlier findings of various Polish researchers from the last 50 years [16,18,30,[39][40][41][42][43][44][45][46]. Similar results have also been obtained outside Poland and even outside Europe [4,13,24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In classical phytopathological studies of various pathogens, research begins with the observation of the development of the disease (symptoms and etiological signs). The observations made during the presented studies fully confirmed the earlier findings of various Polish researchers from the last 50 years [16,18,30,[39][40][41][42][43][44][45][46]. Similar results have also been obtained outside Poland and even outside Europe [4,13,24].…”
Section: Discussionsupporting
confidence: 90%
“…Neither the type of disease symptoms (even if the etiological signs of the pathogen are present) nor anatomical examinations of infested stems allow proper and complete diagnosis of the pathogen [ 29 , 30 ]. For full mycological identification of the causal agent, analysis using artificial culture methods as well as molecular biology methods is necessary [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%